The identification of religious genocide with emphasis on genocide of Shiites / A identificação do genocídio religioso com ênfase no genocídio dos xiitas - Jamadi, Mohammad (REVISTA QUAESTIO IURIS, 2018)
Abstract According to the International Criminal Law and the International Criminal Court, religious genocide is considered as a type of Genocide and the most significant similarity between them is that Religious Genocide is defined as the forced annihilation of religious groups. Because unlike the other instances of genocide, Religious Genocide does not have an official definition in international assemblies, one cannot make a proper judicial distinction between genocide and Religious Genocide. The primary motive behind most of the modern Religious Genocides has been formation of a unified religious-tribal mixture while in the middle ages and during the early modern era, the motive was generally based on mere religion. Results of the present study have shown that according to the article 6 of the statute of the international criminal court, religious genocide is formally identified as a variant of genocide; however there is no clear definition for this villainy. On the other hand, according to the Convention on the Prohibition of Genocide and the statute of the International Criminal Court, crimes against Muslims, especially the Muslims of Myanmar and the Shiites of Yemen and Bahrain are regarded to as explicit instances of Religious Genocide. It is worthy of mentioning that the present study is a descriptive analytical study. Keywords: Genocide, Religious Genocide, Muslims, Shiites, The International Criminal Court. Resumo De acordo com o Direito Penal Internacional e com o Tribunal Penal Internacional, o genocídio religioso é considerado como um tipo de genocídio e a semelhança mais significativa entre eles é que o genocídio religioso é definido como a aniquilação forçada de grupos religiosos. Como, ao contrário dos outros casos de genocídio, genocídio religioso não tem uma definição oficial em assembléias internacionais, não se pode fazer uma distinção adequada por parte das autoridades judiciais entre genocídio e genocídio religioso. O principal motivo por trás da maioria dos genocídios religiosos modernos tem sido a formação de uma mistura religiosa-tribal unificada enquanto na Idade Média e início da era moderna o motivo foi baseado em mera religião em geral. Os resultados do presente estudo mostraram que de acordo com o artigo 6º do Estatuto do Tribunal Penal Internacional, o genocídio religioso é formalmente identificado como uma variante do genocídio; No entanto, não há uma definição clara para essa vilania. Por outro lado, de acordo com a Convenção sobre a Proibição do Genocídio e do Estatuto do Tribunal Penal Internacional, crimes contra os muçulmanos, especialmente os muçulmanos de Mianmar e os xiitas do Iêmen e Bahrein são considerados como explícito caso de genocídio religioso. Vale ressaltar que o presente estudo é um estudo analítico descritivo. Palavras-chave: Genocídio, Genocídio Religioso, Muçulmanos, Xiitas, Tribunal Penal